Urban Heat Island Effects and Mitigation Strategies in Saudi Arabian Cities - Aina, Y.A. (Springer, 2021)
The urban heat island phenomenon is an important factor to be considered in fostering sustainability in urban areas. It has been acknowledged that the phenomenon has relationships with energy consumption, human thermal comfort and general well-being. This chapter examines the effects of urban heat island and the adaptation and mitigation strategies in a desert environment by using Saudi Arabia as a case study. It presents cases of Saudi cities on the issue of UHI and highlights, through a review, the mitigation and adaptation strategies. The strategies include establishing urban green parks, planting trees along road centerlines and implementing public transit projects. It also examines the challenges to these measures. It concludes that more successes can be achieved by exploring other strategies such as cool/green roof and sponge city development. Â© 2020, Springer Nature Singapore Pte Ltd.